Intercepting IRE1 kinase‐FMRP signaling prevents atherosclerosis progression. Issue 4 (22nd February 2022) - Yildirim, Zehra; Baboo, Sabyasachi; Hamid, Syed M; Dogan, Asli E; Tufanli, Ozlem; Robichaud, Sabrina; Emerton, Christina; Diedrich, Jolene K; Vatandaslar, Hasan; Nikolos, Fotis; Gu, Yanghong; Iwawaki, Takao; et al.
Abstract: Fragile X Mental Retardation protein (FMRP), widely known for its role in hereditary intellectual disability, is an RNA‐binding protein (RBP) that controls translation of select mRNAs. We discovered that endoplasmic reticulum (ER) stress induces phosphorylation of FMRP on a site that is known to enhance translation inhibition of FMRP‐bound mRNAs. We show ER stress‐induced activation of Inositol requiring enzyme‐1 (IRE1), an ER‐resident stress‐sensing kinase/endoribonuclease, leads to FMRP phosphorylation and to suppression of macrophage cholesterol efflux and apoptotic cell clearance (efferocytosis). Conversely, FMRP deficiency and pharmacological inhibition of IRE1 kinase activity enhances cholesterol efflux and efferocytosis, reducing atherosclerosis in mice. Our results provide mechanistic insights into how ER stress‐induced IRE1 kinase activity contributes to macrophage cholesterol homeostasis and suggests IRE1 inhibition as a promising new way to counteract atherosclerosis. Synopsis: Targeting IRE1 function and substrate(s) provides a novel therapeutic approach to atherosclerosis. We found a key role for IRE1‐mediated FMRP phosphorylation that suppresses the expression of cholesterol transporters and efferocytosis receptors in macrophages and promotes atherosclerosis progression. FMRP is a novel IRE1 kinase substrate. Lipid‐induced, IRE1‐mediated FMRP phosphorylation leads to post‐transcriptional suppression of cholesterol transporters and efferocytosis regulators. Ablation of IRE1 kinase activity or suppression of FMRP expression enhances efferocytosis and cholesterol transport in vitro and in vivo . IRE1 kinase inhibition by a small molecule inhibitor or genetic deletion of FMRP in macrophages alleviates atherosclerotic plaque formation. Abstract : Targeting IRE1 function and substrate(s) provides a novel therapeutic approach to atherosclerosis. We found a key role for IRE1‐mediated FMRP phosphorylation that suppresses the expression of cholesterol transporters and efferocytosis receptors in macrophages and promotes atherosclerosis progression.